PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION DIDUKUNG METODE RESITASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII SMPN 1 BANGOREJO PADA MATERI FAKTORISASI ALJABAR - Ardiansari, Lia (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2017)
Based on the preliminary study, obtained students' mistakes in completing the algebraic factorization is an indicator that students have learning difficulties that affect the learning results. Learning model that applied  so that learners can understand the overall concept that will eventually be able to improve learning outcomes is Group Investigation, the model of learning that involves students actively in learning because it requires the participation of each member of the group in an investigation. Optimized with recitation that is giving the task to students outside the schedule beyond that which ultimately must be presented to the teacher. Data student learning outcomes at the end of cycle 2 showed that students who scored above the standard minimum completeness or ?75 than the maximum value of 100 is as much as 88%. It can be concluded that the application of the model group supported recitation investigation can improve learning outcomes students of class VIII SMPN 1 Bangorejo.